Culture of Nile tilapia (Oreochromis niloticus) in bacterial biofloc system - JoÃo Henrique Cavalcante Bezerra (2014)
The global production originated from extractive fisheries is stagnant since 2000s. With the increasing global demand for fish products, aquaculture has become one of the main alternatives for the protein supply for human consumption. On the other hand, the intensification of aquaculture production results in an increase of negative impacts on the environment, making necessary the development of new farming technologies that will minimize environmental impacts. The biofloc technology system is proving to be an alternative to traditional cultures, and the great advantage of this system is the reduction of water use, besides the increase in productivity. The objective of this study was to evaluate the growth performance, indexes of water quality, the sustainability indexes of cultures and the economic parameters of Nile tilapia culture at different densities in the bacterial biofloc system. Among the water quality parameters evaluated, ammonia and nitrite showed values above the optimal range used in different densities (200, 400, 600 and 800 fishes m-3), while the values of Total Suspended Solids (TSS) reached the ideal range just after 30 days of culture, an insufficient time to an ideal biological production of flakes and, consequently, the reduction of the nitrogen compounds. Regarding the zootechnical parameters, all showed statistical difference in the four densities experienced, with the density of 600 fishes m-3, presenting the best results in terms of productivity and biomass gain. About the sustainability of cultivation, both the IS and the IQA found were classified as low in all densities, indicating poor water quality of the cultivation. In the economic analysis, there was economic loss at all densities, with the density of 600 peixes.m-3 achieving better results. However, the gross revenue generated was only R$ 124.2 Â 4.2, with a partial operational cost of R$ 166.8 Â 8.7, making necessary the previous establishment of the microbial community in this type of culture system, so that all water quality parameters remain according to ideal standards.